Effect Of Selective Dentin Etching And Ethanol Wet Bonding On Micro-Shear Bond Strength Of Adhesive (Mustansiria Dental Journal, 2025)
Aim: This in vitro study aimed to evaluate the impact of selective dentin etching for 3 seconds and ethanol pre-treatment on the micro-shear bond strength (µSBS) of Scotchbond Plus Universal (SBU), a hydrophilic adhesive containing 2-hydroxyethyl methacrylate (HEMA).Materials and Methods: Forty-eight sound premolars had their occlusal enamel ground to create flattened midcoronal dentin. Teeth were divided into four groups of 12 sample. In Group A (control), SBU plus was applied without prior treatment. Group B involved selective dentin etching with 37% phosphoric acid for 3 seconds. Group C treated dentin surfaces with 100% ethanol for 60 seconds. Group D combined 3-second phosphoric acid etching with 60-second ethanol pre-treatment. The adhesive resin was applied then light cured. Teeth were restored with Filtek Z350 (3M ESPE, USA) composite rods (1mm diameter). After composite placement, samples were stored in distilled water at 37°C for 24 hours and thermocycled for 500 cycles. µSBS was measured using a universal testing machine. Data were analyzed using one-way ANOVA.Results: ANOVA revealed significant differences among the groups (P < 0.001). Group D (selective dentin etching + ethanol pre-treatment) showed the highest µSBS at 57.16 MPa. The number of mixed failures was higher when dentin surfaces were treated with selective etching for 3 seconds and 100% ethanol.Conclusion: Under the conditions of this study, dentin etched with phosphoric acid for 3 seconds and rewetted with 100%